Inwendige Landschaften oder Die leeren Räume der Sprache. Peter Waterhouse’ «Spaziergang als Himmelskunst» und Oswald Eggers «Im Anger des Achilles». Möglichkeiten und Grenzen einer wissenschaftlichen Lektüre (Studia austriaca, 2013)
This essay focuses on two contemporary poems and illustrates both the possibilities and the difficulties of a scholarly reading. Since both poems resist a hermeneutic approach, the essay combines a structural analysis with different poststructural perspectives in the light of concepts proposed by scholars like Derrida, Lacan and Foucault. Instead of trying to understand the “meaning” of the texts, this essay describes the poetic strategies the poems use to evoke an atmosphere of wideness and permeability (Waterhouse) and to create an autonomous poetic reality beyond linguistic standards and logical norms (Egger).